Raspberry PI 3 based of smart system temperature control in greenhouse / Shafiq Nordin - Nordin, Shafiq (2018)
Nowadays, system of plantation in agriculture have a problem to taking care of their production of goods. There are many factor that can be take an attention for certain problem. As an example, there are have problem with condition of the weather and uncertain temperature changes. This project have been plan because there have some problem and difficulty during the plantation. Once of them are quality and production of plant are interrupt the process of industry in a commercial. A few plant need a good maintenance and services that will make sure the quality of plant are guaranteed. From this problem, student have plan and decide to controlling temperature by smart system in greenhouse via android application using raspberry pie. This project are focuses on maintaining the temperature of greenhouse in order to make sure the condition of a plant in a good condition. How this project can help the user to control the temperature of the green house and the plant? This project can, help the user to control the temperature where this system can detect changes of heat occur nearby the house. The user will be notified when any changes occurred and can monitor the green house and plant 24 hours at any time through their Android because a camera and sensor are install inside of the green house. This project also provide a ventilation system and lighting which can be control through the Android application. From the idea and planning, student have expect that it can be develop with smart system successfully. This project was develop to maintain the condition of the surrounding and to maintain the good quality of the plantation.